The application of multirate techniques for synchronization in fully digital demodulation - Han, Wei; Makelainen, Kimmo; Ahmed, Kazi Mohiuddin; Zhang, Jian-Guo; Government of Japan (Bangkok : Asian Institute of Technology, 1995)
This study presents an multirate technique as a timing recovery scheme for digital cellular mobile systems in the digital signal processing environment. n/4-shifted-DQPSK modulation is used according to the North American IS-54 TDMA frame structure. The feasibility of the application of square in-phase and quadrature (SIQ) signal phases as a timing recovery detection signal and their BER performances in fading channels corrupted by CCI and A WGN, are investigated in MATLAB. The phase searching processor is a unit that can extract the appropriate timing instant by comparing the SIQ signal phase with the reference signal phase. The phase adjuster, which is employed to diminish phase distortion caused by fading channel, is used to implement synchronizer design. Its BER performance is measured and compared with the expected performance under various operating conditions, such as two rays Rayleigh fading channel or six bins channel based on the GSM specification, and with interferer from varying power.
Thesis (M.Eng.) - Asian Institute of Technology, 1995
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering.
Keywords: Cellular radio